Kajian Desain Interior Restoran Piazza Italia dan Brandi Pizzeria di Surabaya - Steven Adi Prasetyo (Intra, 2016)
Piazza Italia and Brandi Pizzeria are two of the Specialities Restaurants in Surabaya City, Eastern Java. Piazza Italia and Brandi Pizzeria are two restaurants that particularly serve Italian cuisine with Italian thematic interior design that fits the serving system. The goal of the research is to identify the characteristic of the interior that is applied to the restaurants. Theoretically, this research should be a useful addition to interior academic in terms of standards of interior characteristic in Italian restaurants and how to evaluate them. The atmosphere of the restaurant is built by its aesthetic aspects that are organized visually by means of layout, room-forming elements, room-transition elements, room-filling elements, decorative elements, and lighting systems. This aesthetic aspect is one unity of building and room that is analyzed using four basic theory by Francis D.K. Ching, i.e. functionality, shape, technical, and room theory. On the other hand, cuisine and serving system are analyzed using theories from Soekresno and Marsum. Methods of research used are descriptive analysis to parse the field data that helps the data analysis. The result of the research shows that the interior design application of both restaurants are different in terms of layout composition. Piazza Italia gives a familiar, romantic, and intimate atmosphere by Ala Carte table layout with Fine Dining concept, while Brandi Pizzeria gives the familiar, spacious, and laid-back atmosphere with casual table layout. Big conclusion acquired from this research is that the interior design applied in both Italian restaurant fits the standard of Specialities Restaurant that has thematic interior atmosphere that is adapted to the local condition, thus supporting the serving system of the restaurant. This can keep the quality of both restaurants to satisfy the needs of customers when enjoying the food and atmosphere of the interior applied in the restaurant.